Effect of combining aspirin and rivaroxaban on atherosclerosis in mice. (March 2022) - Grover, Steven P.; Coughlin, Taylor; Fleifil, Salma M.; Posma, Jens J.N.; Spronk, Henri H.M.; Heitmeier, Stefan; Owens, A. Phillip; Mackman, Nigel
Abstract: Background and aims: The platelet inhibitor aspirin reduces inflammation and atherosclerosis in both apolipoprotein E deficient ( apoE −/− ) mice and low-density lipoprotein receptor deficient ( Ldlr −/− ) mice. Similarly, the factor Xa inhibitor rivaroxaban reduces atherosclerosis in both apoE −/− and Ldlr −/− mice. We tested the hypothesis that the combination of aspirin and rivaroxaban reduces atherosclerosis in mice to a greater extent than either agent alone. Methods: Male Ldlr −/− mice were fed a western-type diet for 12 weeks to induce atherosclerosis. Cohorts of mice received aspirin in the water and/or rivaroxaban in the diet. Atherosclerosis and lesion composition were measured in the aortic sinus and the aorta. Expression of 55 proteins in the aorta and plasma was determined using multiplex ELISA assays. Results: Aspirin alone, rivaroxaban alone, and the combination of both agents significantly reduced atherosclerosis in the Ldlr −/− mice compared with control Ldlr −/− mice fed a western-type diet. However, there were no significant differences in atherosclerosis in the group receiving aspirin and rivaroxaban compared with the groups that received aspirin or rivaroxaban alone. Aspirin, rivaroxaban and the combination reduced macrophage content and apoptosis in the lesions compared with controls but there was no difference between the three treatment groups. We observed statistically significant changes in the expression of a small number of proteins in the aorta and plasma in mice treated with aspirin and/or rivaroxaban. Conclusions: Contrary to our expectation, the combination of aspirin and rivaroxaban did not further reduce atherosclerosis in Ldlr −/− mice beyond the level observed with each agent alone. Graphical abstract: Image 1 Highlights: Aspirin and rivaroxaban reduce atherosclerosis in mice. Aspirin and rivaroxaban reduce macrophage content in atherosclerotic lesions. Combining aspirin and rivaroxaban does not further reduce atherosclerosis in mice.